Pembentukan Posyandu Remaja di Pesantren Liwa’ul Haq, Kelurahan Tondo, Kecamatan Talise - Anna Veronica Pont; Olkamien Jesdika Longulo; Mardiani Mangun (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Based on data from Kelurahan Tondo, there are 1170 male teenagers and 1267 female teenagers. 12 people who commit juvenile delinquency.  Adolescents need healthy living skills both physically healthy, mentally and spiritually healthy. The purpose of community service is the establishment of youth posyandu and the organisation of youth posyandu in Tondo village. The Youth Posyandu Establishment method consists of 5 steps, namely: internal approach, external approach, introspective survey, village community deliberation, establishment and monitoring of youth posyandu activities. Teenagers who participated in the activity were 17 people who were teenage posyandu cadres.  Activity Implementation: The preparation stage is 9 June 2022 and the implementation stage is the establishment of posyandu 10 June 2022.  The result of the activity is that the posyandu board at Pesantren Liwa'ul Haq, Tondo village, Palu City, Central Sulawesi Province has been formed. Posyandu activities are carried out every second week of the current month. It is expected that the Youth Posyandu Cadre to be active and arrange posyandu planning every month and motivate adolescents to come to the youth posyandu every month. We suggest that the person in charge of adolescent posyandu at Talise Health Centre provide assistance and guidance in the implementation of adolescent posyandu.